Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Sosial, Kecerdasan Spiritual Dan Beban Kerja Terhadap Kinerja Pegawai Pada Balai Besar Pengawas Obat Dan Makanan (BBPOM) Di Mataram - Annisa Aprilia; Santi Nururly (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to determine the effect of Intellectual Intelligence, Emotional Intelligence, Social Intelligence, Spiritual Intelligence and Workload on Employee Performance at the Center for Drug and Food Control (BBPOM) in Mataram. The population in this study were employees of the Center for Drug and Food Control (BBPOM) in Mataram in the field of testing and inspection, totaling 43 employees using Non Probability Sampling (Purposive Sampling) where the sample can represent the characteristics of the desired population. Data processing in this study uses SEM – PLS (Structural Equation Modeling – Partial Least Square). Based on the research results, intellectual intelligence has a significant effect on employee performance, emotional intelligence has a significant effect on employee performance, social intelligence has a significant effect on employee performance, spiritual intelligence has a significant effect on employee performance and workload has a significant effect on employee performance. the most dominant variables that affect the variables of intellectual intelligence, spiritual intelligence, social intelligence, and emotional intelligence.